(untitled) (International journal of medical sciences, 2026)
Antibiotics are among the most important therapeutic agents for the treatment of bacterial infections, and their role in modern medical practice is invaluable. However, the widespread and uncontrolled use of antibiotics can lead to significant disruption of the normal bacterial microflora of the human body. This article reviews the effects of antibiotics on the intestinal, skin, and mucosal microflora, the mechanisms of dysbiosis development, and the processes involved in the formation of antibiotic-resistant microorganisms, based on both Uzbek and international scientific sources. During the study, the impact of β-lactams, macrolides, aminoglycosides, and fluoroquinolones on the composition of the microbiota was analyzed. The results indicate that broad-spectrum antibiotics cause a reduction in beneficial microorganisms and promote the overgrowth of opportunistic pathogenic bacteria. Studies conducted by Uzbek researchers have also reported the development of intestinal dysbiosis, weakened immune responses, and metabolic disturbances following antibiotic therapy. The article emphasizes the importance of rational antibiotic use and highlights the role of probiotics and prebiotics in restoring the balance of the normal microflora.